Istirātījiyyat Ta’allum al-‘Arabiyyah ‘Alā Dhau’i Asalīb at-Ta’allum fī Markaz al-Lughah bi Jāmi’ati Antasari al-Islāmiyyah al-Hukūmiyyah Banjarmasin - Lailatun Nazifah; Faisal Mubarak Saif; Ridha Darmawaty (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2021)
Learning strategies play a crucial role in the success of the learning process, while learning styles significantly influence students’ academic performance and learning outcomes. This study aims to identify and describe the Arabic language learning strategies employed by students based on their individual learning styles. A qualitative research design was adopted, involving 20 students from UPB Group 22 in the 2019 academic year as the research participants. Data were collected through questionnaires and semi-structured interviews and analyzed using descriptive qualitative techniques, including data reduction, data display, and conclusion drawing. The findings reveal that students with a visual learning style prefer learning through visual representations, such as colors, diagrams, and written texts, which facilitate comprehension and information retention. These students tend to remember what they see more effectively than what they hear and generally prefer reading independently rather than listening to information. In contrast, students with an auditory learning style rely primarily on listening to acquire knowledge. They demonstrate better recall of spoken information, prefer reading aloud, and often experience difficulty when completing tasks that require strong visual processing. Meanwhile, students with a kinesthetic learning style learn most effectively through physical engagement and hands-on activities. They understand concepts more easily by practicing, experimenting, and interacting directly with objects rather than by reading or listening alone. These findings highlight the importance of aligning instructional strategies with students’ dominant learning styles to enhance the effectiveness of Arabic language teaching and improve learning outcomes.